加味復元通氣散의 항염작용에 대한 실험적 연구 - 김지혜(Ji Hye Kim); 임현정(Hyun Jung Lim); 신선미(Sun Mi Shin); 김수민(Soo Min Kim); 이정은(Jung Eun Lee); 유동열(Dong Youl Yoo) (동의생리병리학회지, 2007)
The purpose of this research was to investigate the anti-inflammatory effects of Kamibokwontonggi-san(KBTS) which has been medicated the patient such as mastitis, mammary tuberculosis. KBTS in RAW264.7 cell inhibited IL-1β, IL-6, TNF-α, COX-2 and NOS-II mRNA genes expression in a concentration-dependent manner. KBTS inhibited NO production significantly at 100, 50 ㎍/㎖ and ROS production in a concentration-dependent manner. KBTS inhibited IL-1β, IL-6 and TNF-α production significantly in serum of acute anti-inflammation-induced mice and the survival rate at the 3rd day on LPS-induced lethal endotoxemia. These results suggest that Kamibokwonntonggi-san (KBTS) can be useful in treating a lot of women diseases caused by inflammation such as mastitis, mammary tuberculosis, pelvic inflammatory disease and pelvic tuberculosis. KCI Citation Count: 2